A Comparison of Nursing Core Competency Frameworks in ASEAN Countries: A Document Analysis - Mohamad As’ad Efendy; Michael I. Aggari (Journal Of Nursing Practice, 2025)
Background: The nursing profession in Southeast Asia is facing growing complexity due to demographic shifts, changing disease patterns, and rising demands for high-quality care. Regional efforts to enhance workforce mobility and standardize qualifications have led to the development of core competencies in common nursing. However, the national implementation remains inconsistent. Purpose: This study aimed to compare national nursing competency frameworks across ASEAN countries and to assess their alignment with the ASEAN regional core competency framework. Methods: Qualitative document analysis was conducted using national nursing competency frameworks, policy reports, and regulatory documents published between 2010 and 2023. Data were analyzed through deductive coding against regional competency domains and inductive identification of structural and thematic variations. Results: The study reviewed ten national frameworks and found substantial variations in structure and emphasis. Domains related to ethics and clinical practice were commonly addressed, whereas leadership and research were less consistently included. More recent frameworks showed a stronger alignment with regional standards, while older ones reflected a limited competency scope. Key challenges include regulatory fragmentation, inconsistent assessment systems, and gaps in education capacity. Conclusion: The findings highlight the need for greater regional policy coordination, the development of shared assessment tools, and investment in capacity building. Harmonizing nursing competencies across ASEAN countries is essential for improving educational consistency, patient care quality, and professional mobility.